The accumulation of sanctions from the perspective of decriminalized administrative offenses: an analysis of the italian punitive model - Farias Puerari, Adriano (2024)
This article examines the cumulative nature of sanctions from the perspective of the administrative offense decriminalized in the Italian punitive model. It begins with an approach to the historical evolution of Sanctioning Administrative Law and its relationship with Criminal Law, highlighting how both derive from the state jus puniendi, through the analysis of the differentiating, unitary, and mixed theory in relation to criminal and administrative offenses. It moves forward to address Law No. 689/81, a milestone in this process in Italy, which converted several criminal offenses into administrative offenses and established an autonomous regime parallel to criminal law. In the European country, through the 1983 Circular of the Presidency of the Council of Ministers, the choice between sanctions is guided based on the principles of proportionality and subsidiarity. The Italian model, known as doppio binario, thus encompasses a degree of communicability between the different punitive spheres, avoiding overlapping sanctions for the same fact. The conclusion is that the distinction between criminal and administrative offenses must be guided by proportionality, with an intermediate gray area that requires legislative consideration, highlighting the complementarity between sanctioning systems.